A NOVEL SPLICE-SITE MUTATION ON THE MLC1 GENE LEADING TO EXON 9 SKIPPING AND MEGALENCEPHALIC LEUKOENCEPHALOPATHY WITH SUBCORTICAL CYSTS IN A TURKISH PATIENT - TÜRKDOĞAN, DİLŞAD (MACEDONIAN ACAD SCIENCES ARTS, 2019)
Megalencephalic leukoencephalopathy (MLC) with subcortical cysts, also known as Van der Knaap disease (MIM #604004) is an autosomal recessive neurological disorder characterized by early onset macrocephaly, epilepsy, neurological deterioration with cerebellar ataxia and spasticity. An 8-month-old boy was admitted to our pediatric neurology clinic with macrocephaly. His brain magnetic resonance imaging (MRI) revealed bilateral, diffuse, symmetric structural white matter abnormalities, relatively sparing the cerebellum and bilateral subcortical temporal cysts. The diagnosis of Van der Knaap disease was suspected based on the clinical features and imaging findings and the genetic analysis revealed a novel homozygous c.768+2T>C mutation of the MLC1 gene. For determination of the novel splice-site mutation's effect, cDNA amplification was performed. cDNA analysis showed that the splice-site c.768+2T>C mutation gave rise to exon 9 skipping.
Keywords: cDNA sequencing; Exon skipping; Leuko-encephalopathy; MLC1 gene; Splice-site mutation